The Development Status and Cultivation Pathway of Rural Elites’ Spirit Among Public-Funded Teacher Trainees - Yan, Chuang (Journal of Advanced Research in Education, 2025)
Under the Rural Revitalization Strategy, Public-Funded teacher trainees serve as a core force in revitalizing rural education. Cultivating their spirit of rural elites is crucial for preserving rural culture and enhancing educational quality. This study employed a self-developed “Rural Elites’ Spirit Scale for Public-Funded Teacher Trainees” (Cronbach’s α = 0.980) to conduct an empirical survey of 539 such trainees in Guangdong Province of China, systematically analyzing the development status across six dimensions. Key findings reveal: (1) While the overall level of rural elites’ spirit is favorable (M = 4.241), significant structural imbalances exist across dimensions: Gentleman Spirit (M = 4.412) and Teacher’s Spirit (M = 4.281) are notably strong, whereas Dedication Spirit demonstrates significant weakness (M = 4.039) and exhibits the largest individual variation (SD = 0.715). (2) Significant differences exist based on rural/urban background: Trainees from rural backgrounds outperformed their urban counterparts in Dedication Spirit, Sincerity Spirit (Filial Piety), Gentleman Spirit, and Teacher’s Spirit (p = .015, p = .043, p = .048, p = .050, respectively), as well as in the total score (p = .024). (3) Insufficient post-service development motivation: No significant differences were found between current students and graduates across all dimensions and the total score (p > .05), indicating a lack of effective mechanisms for cultivating the spirit after employment. (4) Strong synergistic effects across dimensions: Significant positive correlations were observed among all dimensions (r = .635 - .908), with particularly strong correlations between Sincerity Spirit and Inheritance Spirit (r = .908) and between Sincerity Spirit and Dedication Spirit (r = .842), suggesting an emotion-driven synergistic network. Based on these findings, we propose a “Three-Dimensional Drive” cultivation pathway: addressing the deficit in Dedication Spirit through curriculum reconstruction; implementing tiered empowerment strategies to bridge group disparities; and leveraging dimensional synergy effects through integrated project-based learning. This research provides empirical evidence for addressing the dilemmas of “inability to retain” and “inability to teach effectively” among rural teachers and holds significant policy implications for strengthening the ethical foundation of educational revitalization.